Anticancer Perspectives on the Fungal-Derived Polyphenolic Hispolon - Islam, Muhammad T.; Ali, Eunus S.; Khan, Ishaq N.; Shaw, Subrata; Uddin, Shaikh J.; Rouf, Razina; Dev, Shrabanti; Saravi, Seyed S.S.; Das, Niranjan; Tripathi, Swati; Yele, Santosh U.; Das, Asish K.; et al. (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: Cancer is a dreadful disease causing thousands of deaths per year worldwide, which requires precision diagnostics and therapy. Although the selection of therapeutic regimens depends on the cancer type, chemotherapy remains a sustainable treatment strategy despite some of its known side-effects. To date, a number of natural products and their derivatives or analogues have been investigated as potent anticancer drugs. These drug discoveries have aimed for targeted therapy and reduced side-effects, including natural therapeutic regimens. Objective: This review introduces a prospective fungal-derived polyphenol, Hispolon (HIS), as an anticancer agent. Accordingly, this review focuses on exploring the anticancer effect of hispolon based on information extracted from databases such as PubMed, ScienceDirect, MedLine, Web of Science, and Google Scholar. Methods: A literature search in PubMed, ScienceDirect, MedLine, Web of Science, and Google Scholar was accomplished, using the keyword ‘Hispolon’, pairing with ‘cancer’, ‘cytotoxicity’, ‘cell cycle arrest’, ‘apoptosis’, ‘metastasis’, ‘migration’, ‘invasion’, ‘proliferation’, ‘genotoxicity’, ‘mutagenicity’, ‘drug-resistant cancer’, ‘autophagy’, and ‘estrogen receptor. Results: Database-dependent findings from reported research works suggest that HIS can exert anticancer effects by modulating multiple molecular and biochemical pathways, including cell cycle arrest, apoptosis, autophagy, inhibition of proliferation, metastasis, migration, and invasion. Moreover, HIS inhibits the estrogenic activity and exhibits chemoprevention prospects, possibly due to its protective effects such as anticancer and anti-inflammatory mechanisms. To date, a number of HIS derivatives and analogues have been introduced for their anticancer effects in numerous cancer cell lines. Conclusion: Data obtained from this review suggest that hispolon and some of its derivatives can be promising anticancer agents, and may become plant-based cancer chemotherapeutic leads for the development of potent anticancer drugs, alone or in combination with other chemotherapeutic agents.
Keywords: Polyphenol